Patients with Metabolic Syndrome Have Prolonged Corrected QT Interval (QTc) - Li, Weiju (Clin Cardiol, 2009)
BACKGROUND: Prolongation of corrected QT interval (QTc) increases morbidity and mortality and QTc has been found to be longer in patients with diabetes mellitus than in healthy controls. It is still inconclusive whether the metabolic syndrome results in QTc prolongation. HYPOTHESIS: We hypothesized that metabolic syndrome might contribute to risk of QTc prolongation. The hypothesis was tested in a large population. METHODS: A total of 5,815 individuals (men: 1,950, women: 3,865 aged 20–80 years) were enrolled. Metabolic syndrome was defined according to the revised third National Cholesterol Education Program Adult Treatment Panel (NCEP‐ATP III). QTc was calculated by using Bazett and Fridericia equations and the corrected JT interval (JTc) was derived by subtracting the QRS duration from the QTcB. All individuals had physical examinations, electrocardiograms, echocardiography, and blood tests. RESULTS: Individuals with metabolic syndrome had longer QTcs and JTc than those without metabolic syndrome (439.84 ms versus 430.90 ms in men, 456.37 ms versus 445.12 ms in women, respectively, p < 0.001 using Bazett formula). The more the number of abnormal metabolic parameters they had, the longer the QTcs and JTc they had. Trend analysis indicated that QTcB, QTcF, and JTc were significantly correlated to the number of abnormal metabolic parameters both in men and in women. After being adjusted for conventional risk factors, QTcB, QTcF, and JTc remained negatively associated with serum potassium concentration and positively associated with interventricular septal thickness. CONCLUSIONS: Metabolic syndrome is a risk factor for prolonged QTc, which may further increase cardiovascular morbidity and mortality in the subjects with metabolic syndrome. Copyright © 2009 Wiley Periodicals, Inc.